Analisis Penerapan Profil Pelajar Pancasila Pada Mata Pelajaran SBdP Kelas IV Sekolah Dasar - Nabila Arkha Zhakina; Yun Ratna Lagandesa; Pahriadi Pahriadi; Kadek Hariana; Ryan Andhika Pratama (Attadrib: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2025)
The purpose of this research is to analyze the implementation of the Pancasila Student Profile through Cultural Arts and Crafts Education (SBdP) in Grade IV at SD Inpres Boyantongo. The method used is descriptive qualitative, with data collection techniques including observation, interviews, and documentation. The subjects of the research consist of the Grade IV teacher and Grade IV students as supporting subjects to identify the supporting and inhibiting factors in the implementation of the Pancasila Student Profile. The results of the study indicate that the application of the values of the dimensions within the Pancasila Student Profile in the Cultural Arts and Crafts Education subject has been effectively implemented. During the learning process, the teacher applied the six dimensions of the Pancasila Student Profile, which are Faith and Devotion to God Almighty, Global Diversity, Mutual Cooperation, Independence, Critical Reasoning, and Creativity. Religious values and manners are evident in the students' habits of praying and showing respect. In the dimension of global diversity, the teacher created an open classroom atmosphere conducive to discussion. Group activities demonstrated cooperation, while the dimension of independence was observed when students completed individual tasks. The challenges faced included limited learning resources and reading abilities. The teacher employed methods that encouraged active student participation and aimed to develop students' character comprehensively. The SBdP learning can serve as an effective medium for instilling the values of the Pancasila Student Profile if implemented consistently with support from all parties.